2013
DOI: 10.1111/eci.12163
|View full text |Cite
|
Sign up to set email alerts
|

Distinct genetic aberrations in oesophageal adeno and squamous carcinoma

Abstract: Our results reveal the presence of distinct aberrations in oesophageal adenocarcinoma and squamous cell carcinoma which are replicated in the respective components of adenosquamous cancers. The study therefore suggests perhaps an independent origin of the two components of oesophageal adenosquamous mixed cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
31
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 24 publications
(31 citation statements)
references
References 24 publications
0
31
0
Order By: Relevance
“…IHC was performed as per standard protocols [7] on tissues embedded into FFPE blocks mentioned above, as per standard practice though we are aware that this slice of tissue may not represent the whole tumor. 4 μM tumor sections were deparafinized and rehydrated in graded series of alcohol followed by heat induced epitope retrieval in citrate buffer at pH 6.0 (for p53) or proteinase K pretreatment (for epidermal growth factor receptor (EGFR)) and subjected to peroxidase quenching using 0.6% hydrogen peroxide in methanol.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…IHC was performed as per standard protocols [7] on tissues embedded into FFPE blocks mentioned above, as per standard practice though we are aware that this slice of tissue may not represent the whole tumor. 4 μM tumor sections were deparafinized and rehydrated in graded series of alcohol followed by heat induced epitope retrieval in citrate buffer at pH 6.0 (for p53) or proteinase K pretreatment (for epidermal growth factor receptor (EGFR)) and subjected to peroxidase quenching using 0.6% hydrogen peroxide in methanol.…”
Section: Methodsmentioning
confidence: 99%
“…Suspected in-dels were confirmed using TA cloning vector (Invitrogen, Carlsbad, CA, USA) as per standard procedure. PCR based screening of HPV was carried out as per standard protocol [7] with GP5 + and GP6 + primers using DNA isolated from frozen tumor tissue as template. Primer sequences are given in supplementary Additional file 2: Table S2.…”
Section: Methodsmentioning
confidence: 99%
“…In colorectal adenocarcinoma, the Bethesda panel mentioned above, was developed for detecting hereditary non-polyposis colorectal cancer at National Cancer Institute-sponsored MSI workshop in 1997 [10]. To our best knowledge, there are 16 studies that investigated the MSI status, focusing on EGJ adenocarcinoma (Table 1) [12][13][14][15][16][17][18][19][20][21][22][23][24][25][26][27]. All those studies used genetic testing.…”
Section: Previous Studies Examining Msi Status In Egj Adenocarcinomamentioning
confidence: 99%
“…An evaluation of whole-tumor sections from a subset of 45 tumors revealed that the frequency of PD-L1 positive immune cells was somewhat higher [35.6% (16/45) of cases, of which 7/16 were not identified on the TMA], although still lower than that reported in GC. Interestingly, Barrett'sassociated EAC has been reported to have a low frequency of MSI and EBV (see below) (37,38).…”
Section: Pd-l1 Expression In Gastro-esophageal Tumorsmentioning
confidence: 99%
“…MSI was detected in 6.6% (5/76) of patients with Barrett'sassociated EAC, with the presence of MSI limited to AC cells, and not in adjacent Barrett's or normal epithelia (37,38). MSI has been less well studied in ESCC, although it has been detected in a subset of patients (110)(111)(112).…”
Section: Mismatch Repair (Mmr) Deficiency and Hypermutation In Gastromentioning
confidence: 99%